Developing the Socially Useful Economy - Bodington, Stephen. author. aut Link
IX, 263 p.
Keywords: "[Based on a series of] seminars ... organised by CAITS (Centre for Alternative Industrial and Technological Systems) and Middlesex Polytechnic staff [in 1984]"--P. ix.